Pendidikan Inklusi: Gangguan Keterlambatan Bicara (Speech Delay) pada Siswa SDN Sukasari 5 - Nurfadhillah, Septy; Riswanti, Cyintia; Mufliha, Dede; Solatun, Saomi (Lembaga Yasin AlSys, 2022)
Children's language gradually develops according to the stimulation given by parents, teachers and society. The language development of children aged 6-12 years can be seen through speaking fluently, mastery of language and delivery of words is more complex. This study aims to identify cases of children who are late to speak, to find out the efforts of teachers and parents in overcoming children who are late to speak and to design a concept model for developing language skills of children who are late speaking. The approach used in this study is a qualitative descriptive approach. Data sources consist of: subjects (children, teachers, parents and speech therapists). Data was collected through observation, and interviews. The results showed that there were children who were late in speaking at the age of 6-12 years at the Sukasari 5 State Elementary School with a type of speech and language expressive disorder. Factors that affect children's speech delay consist of: intelligence, use of a second language, speech style/model that is imitated, health, and family relationships. The concept of the model that the researcher offers in this study is in the form of strategies/techniques to overcome speech delays in children, namely: training children to speak correctly, slowly and repeatedly, when speaking always pay attention to the grammar spoken, always involving children in speaking in every situation by improving children's pronunciation is still wrong, and using several systems such as regular consultations to find out the child's development to doctors and child psychologists.